Growing condition variations and grain prices in Niger and Nigeria - Hatzenbuehler, Patrick L.; Abbott, Philip C.; Abdoulaye, Tahirou (Oxford University Press, 2020)
In this paper, we describe how both the existing degree of price correspondence and tradability are important factors explaining why and the extent to which grain price relationships adjust due to growing condition variations. For a set of maize and millet markets in Niger and Nigeria with different agro-ecological characteristics and strengths of price relationships, we use normalised difference vegetation index (NDVI) data to identify years with weather-related production shocks. We then measure the degree to which price transmission between the commercial hub and reference market in each country in the anomalous weather years varies from that in normal years.